2013
DOI: 10.7448/ias.16.1.18633
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of chronic lung disease in HIV‐infected children and adolescents

Abstract: Until recently, little attention has been given to chronic lung disease (CLD) in HIV-infected children. As the HIV epidemic matures in sub-Saharan Africa, adolescents who acquired HIV by vertical transmission are presenting to health services with chronic diseases. The most common is CLD, which is often debilitating.This review summarizes the limited data available on the epidemiology, pathophysiology, clinical picture, special investigations and management of CLD in HIV-infected adolescents. A number of assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…50 The range of chronic lung disease seems to differ in adolescents compared with younger children. 51 In a study from Zimbabwe of 116 adolescents with HIV infection acquired perinatally, more than 30% of children had severe and disabling chronic respiratory symptoms; these findings were confirmed by those of a study from Malawi in 160 older children. 52 Unexpectedly, in the Zimbabwe study, high-resolution CT scanning showed predominantly small-airways disease consistent with constrictive obliterative bronchiolitis, with lymphocytic interstitial pneumonitis being an exceptional finding.…”
Section: Chronic Diseasementioning
confidence: 69%
See 1 more Smart Citation
“…50 The range of chronic lung disease seems to differ in adolescents compared with younger children. 51 In a study from Zimbabwe of 116 adolescents with HIV infection acquired perinatally, more than 30% of children had severe and disabling chronic respiratory symptoms; these findings were confirmed by those of a study from Malawi in 160 older children. 52 Unexpectedly, in the Zimbabwe study, high-resolution CT scanning showed predominantly small-airways disease consistent with constrictive obliterative bronchiolitis, with lymphocytic interstitial pneumonitis being an exceptional finding.…”
Section: Chronic Diseasementioning
confidence: 69%
“…29 Obliterative bronchiolitis, which occurs with graft-versus-host disease and after viral infections and exposure to chemical fumes, is a progressive life-threatening condition, and little is known about its natural history and pathogenesis in people with HIV infection or how it should be managed. 51,53 Chest radiographic findings are non-specific, and high-resolution CT—the gold standard diagnostic method—is not typically available in resource-limited settings. 53 Obliterative bronchiolitis has not been described before in US and European cohorts of HIV-infected adolescents.…”
Section: Chronic Diseasementioning
confidence: 99%
“…Although corticosteroids are often available at a district hospital for children with LIP showing severe dyspnea, cyanosis, or hypoxia, this is often not the routine practice when the diagnosis is unclear or when clinicians are not experienced in managing clinical complications in children [81,82]. LIP has been shown to respond well to ART, but remains an important clinical consideration, especially in settings with low coverage of ART for HIV-infected children [83]. …”
Section: Health Systems Gapsmentioning
confidence: 99%
“…Respiratory disease is the most common manifestation of HIV/AIDS among children, accounting for more than 50% of HIV-associated mortality [14]. The use of antiretroviral therapy (ART) and co-trimoxazole prophylaxis has contributed to a reduction in the rate of acute respiratory tract infections and mortality among HIV-infected children in both high-resource and low-resource settings [5].…”
Section: Introductionmentioning
confidence: 99%